THE NEED AND THE POSSIBILITIES OF THE HUMAN CAPITAL DEVELOPMENT: ASSESSMENT OF EMPLOYERS AND GRADUATES OF HIGHER EDUCATION INSTITUTIONS - Neverauskienė, Laima Okunevičiūtė; Gruževskis, Boguslavas (Ekonomika, 2009)
The article analyses the problem of human/intellectual capital in the context of the integration of an individual into the labour market, the role of human capital in the activity of enterprises (organizations). According to the information of the Department of Statistics on adult education,and data of sociological research (results of the research of employers and graduates working in their enterprises) the development of human capital, the need and the investment possibilities are assessed in Lithuania.